Enhancing HEI’s Performance: The Strategic Role of Accreditation and Motivation - farwitawati, Reni; Fithrie, Souvya; Masirun, Masirun (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the effect of accreditation on higher education institutions (HEI’s) performance with motivation as a mediating variable. The main research question addresses how accreditation contributes to improving HEI’s performance, both directly and through enhancing lecturers’ motivation. The research employed a quantitative approach using Partial Least Square Structural Equation Modeling (PLS-SEM) based on data collected from 342 lecturers under LLDIKTI 17. The findings indicate that accreditation has a positive and significant effect on both HEI’s performance and lecturers’ motivation, while motivation also significantly influences HEI’s performance. Furthermore, motivation was found to mediate the relationship between accreditation and performance, highlighting the psychological role of academic staff in implementing institutional quality standards. The results suggest that efforts to improve accreditation quality should be accompanied by strategies to strengthen motivation in order to achieve sustainable institutional performance excellence. This study contributes theoretically to the development of performance models grounded in the Resource-Based View (RBV) framework and offers practical implications for higher education management in designing effective quality assurance and incentive policies